Digital transformation in HR Planning: Adaptation strategies and challenges in the industrial revolution 5.0 era - Ramadian, Afzil; Nurlinda, Della Zulfia; Ramadhina, Novy (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
Digital transformation has become a global phenomenon that affects various aspects of business, including human resource (HR) planning. The Industrial Revolution 5.0 era requires organizations to integrate advanced technologies such as artificial intelligence (AI), Internet of Things (IoT), and big data into the HR planning process. This study aims to explore adaptation strategies and challenges faced by organizations in facing digital transformation in the field of HR planning. The research method used is qualitative with a literature study approach and secondary data analysis from indexed journals. The results of the study show that digital transformation offers opportunities to improve the efficiency and accuracy of HR planning, but also presents challenges such as employee resistance, skills gaps, and ethical issues. The conclusion of this study is that organizations need to develop a holistic strategy that includes training, organizational culture change, and collaboration with stakeholders to adapt to the Industrial Revolution 5.0 era.